PENGARUH KEPUASAN KERJA DAN MOTIVASI TERHADAP KINERJA KARYAWAN PT PIZZA HUT CABANG JATIWARINGIN HANKAM - Nila Dewi Aschari; Donny Dharmawan (Jurnal Ekonomi dan Industri, 2022)
This study aims to analyze the effect of job satisfaction and work motivation on employee performance PT. Pizza Hut cabang Jatiwaringin Hankam. The research method used in this study is the causal association method and uses a quantitative approach. The population in this study were employees of PT. Pizza Hut Jatiwaringin Branch. Using a saturated sample is a sampling technique, where all members of the population are sampled. The method of analysis used simultaneous linear regression. Job satisfaction and motivation simultaneously have a significant effect on employee performance.